PAP Polypeptide Promotes Osteogenesis in Jaw Bone Defect Repair by Inhibiting Inflammatory Reactions - Guo, Ke; Zhao, Haoming; Chen, Guokun; Zhang, Ying; Wang, Yu; Huo, Liang; Sun, Shoufu; Wei, Wenjia (Frontiers in Bioengineering and Biotechnology, 2022)
Jaw defects are common in oral and maxillofacial diseases and require surgical repair in extreme cases. Given the limitations in availability and efficacy of autologous bone grafts or allografts, great effort has been made in finding suitable, biocompatible, and effective artificial bone materials. Considering the key role of inflammation in bone resorption, we sought to identify a polypeptide with anti-inflammatory and bone-promoting effects. Rat bone marrow-derived mesenchymal cells (BMSCs) were treated with lipopolysaccharide (LPS) to induce an inflammatory environment, and 1,538 differentially abundant polypeptides were identified using mass spectrometry. Based on mass spectrometry signal intensity, multiple of difference, and structural stability, PAP was screened out as the polypeptide with the lowest abundance in the inflammatory condition. PAP showed no cytotoxicity to BMSCs with increasing concentrations. PAP (10 μM) also increased alkaline phosphatase activity and mRNA expression of Ocn, Bmp2, and Runx2 in a concentration-dependent manner, which confirmed that it can promote osteogenic induction of rat BMSCs. Moreover, PAP reduced LPS-induced expression of inflammatory cytokines (TNF-α, IL-1β, IL-6) and reactive oxygen species and inhibited polarization of RAW 264.7 macrophages to the inflammatory type. Finally, a skull defect mouse model was established, and mice were injected with LPS and/or PAP. Micro-CT, histological analysis, and immunohistochemical staining showed that PAP significantly reduced the number of LPS-induced bone resorption pits and maintained bone integrity. Overall, the polypeptide PAP screened using LPS stimulation of BMSCs is not cytotoxic and can inhibit the inflammatory reaction process to promote osteogenesis. This study thus provides a basis for development of PAP as a new osteogenic material in the repair of jaw defects.